2019
DOI: 10.1128/aac.00707-19
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Membrane Integrity by the Bacterium-Derived Antifungal Jagaricin

Abstract: Jagaricin is a lipopeptide produced by the bacterial mushroom pathogen Janthinobacterium agaricidamnosum, the causative agent of mushroom soft rot disease. Apart from causing lesions in mushrooms, jagaricin is a potent antifungal active against human-pathogenic fungi. We show that jagaricin acts by impairing membrane integrity, resulting in a rapid flux of ions, including Ca2+, into susceptible target cells. Accordingly, the calcineurin pathway is required for jagaricin tolerance in the fungal pathogen Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
(82 reference statements)
1
19
0
Order By: Relevance
“…In another study published in 2019, the lipopeptide jagaricin produced by a bacterial fungal pathogen showed fungicidal effects against human pathogenic fungi by disrupting membrane integrity. They also found that deletions in the ERG5 and ERG6 genes did not affect the susceptibility of Candida albicans and Candida glabrata to jagaricin ( Fischer et al, 2019 ).…”
Section: Natural Products With Antifungal Activitymentioning
confidence: 99%
“…In another study published in 2019, the lipopeptide jagaricin produced by a bacterial fungal pathogen showed fungicidal effects against human pathogenic fungi by disrupting membrane integrity. They also found that deletions in the ERG5 and ERG6 genes did not affect the susceptibility of Candida albicans and Candida glabrata to jagaricin ( Fischer et al, 2019 ).…”
Section: Natural Products With Antifungal Activitymentioning
confidence: 99%
“…The B. thuringiensis isolates from both principal and alternate sympatric hosts are broadly aggressive to potential saprophytic invaders, including fungi and nematodes. One possible factor is their hemolytic ability [42][43] . In comparison with non-hemolytic Bacillus, hemolytic B. thuringiensis isolates displayed higher fatal effects to free-living nematodes and growth inhibition of co-cultured entomopathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria from the inside of the ant host were released by homogenizing the ant host in 200 μL water and culturing on LB agar plates at 28°C for two days. Approximately 45 (43)(44)(45)(46) isolates were randomly picked from each plate with sterile toothpicks, and were suspended in the LB medium supplemented with 15% v/v glycerol and maintained at -80°C until the time of examination. In total, 247 bacterial isolates from P. moesta and 241 bacterial isolates from P. wol were collected.…”
Section: Isolation and Cultivation Of Bacteriamentioning
confidence: 99%
“…al cultured the bacterium quasi-naturally on mushroom slices, and thereby induced the expression of the cryptic gene cluster that allowed production of jagaracin, which in turn was detected by imaging mass spectrometry [99] . Notably, jagaricin exhibited a broad spectrum of activity against plant fungal pathogens, making it a promising starting point for a compound that may be useful in agriculture [100] .…”
Section: Introductionmentioning
confidence: 99%